Zagadnienia inkulturacji w Afryce w okresie powstania orędzia Africae terrarum Pawła VI - Halemba, Andrzej (Śląskie Studia Historyczno-Teologiczne, 1993)
The Church, in its work of evangelization, has always had the rule never to condemn, destroy or abandon any element belonging to the cultural heritage which was, in itself, beautiful, just and true. This rule was explicitly expressed by Pius XII in Evangelii praecones (1951). However this document did not deal fully with all the issues and problems which were being experienced in the missionary Church at that time. The most important issue was to create a new model of mission based on the inculturation of the faith. This inculturation, which involves both the missionary and the people evangelised, could be described as the conscious and progressive assimilation of cultural values in the process of evangelization. The problem of inculturation in Africa emerged most clearly just after the Vatican Council. (Although the term „inculturation” had been used previously by other authors, it is only in 1979, in Catechesi tradendae of John Paul II, that it appeared for the first time in a papal document). An important document on the subject of evangelization in Africa was the papal message Africae terrarum which dealt with the development issues and with other difficulties being experienced in Africa. In this message there was an evaluation of the activities of the Church in that continent. It stressed the fact that a local hierarchy had been established and it spoke of the great contribution of the Church in the field of education. During the sixties (when most countries got their independence) the situation changed considerably because the Church lost its control over its schools. And because of that the Church had to focus its efforts on evangelization alone. While these changes were taking place, there was a greater perception of many of the mistakes of the past, especially of the underestimation by the Church of the local customs and of the religious attitudes and values. Consequently, in this period the discussion on inculturation became more lively. As well as the Church's loss of influence through the schools, there were other factors which made it clear that its pastoral methods had to be changed: the drop in priestly vocations; the deterioration of the political situation and the outbreak of civil wars in some of the young African countries, the conflict between ideologies and nationalism. All these facts had a great influence on the Church and contributed to a slowing down of the progress of evangelization. At that moment, therefore, it was considered necessary that the Pope take a stand on this topic. In the encyclical Popolorum progressio Paul VI spoke about the changes taking place in the world and described the elements which make for the integral progress of the individual human person as well as of humankind in general. A few months later, in his message Africae terrarum, he stressed that the African person does not need to deny his identity or discard his traditions when he joins the Christian community. According to this message the responsibility for the work of inculturation belongs to the local Church hierarchy. However, co-operation between the missionaries and the African clergy is absolutely necessary. The full inculturation of the Christian faith also requires political peace and stability; therefore politicians, governments and intellectuals are to be involved. The Pope invited the family to be fully involved in this process, and he dealt at some length with the special role of women and of the youth. True inculturation of the faith should lead the Christian family to the acceptance of values which will manifest the dignity of each person and will guarantee his or her integral development. Through authentic inculturation the values of the local culture will be brought to their fulfilment. „The African culture”, said cardinal Paul Poupard, „is a wonderful soil which is awaiting the incarnation of Christ. Inculturation, then, is a real form of the solemn covenant between God and man, which is taking place here and now and which is embracing the practical aspects of daily life, the different forms of thought and of social institutions”. Inculturation, being a dialogue between cultures and faith, is a process which is mutually enriching both for the Church and for the people evangelised. The Church accepts all the cultural elements which are compatible with the Good News and enriches them with the Christian message and, at the same time, the Church is enriched by the wisdom of those cultures. We hope that the inculturation of the faith which was started in the late sixties will be deepened and developed during the African Synod, which is not only an opportunity for the Church in Africa but also for the universal Church.